2020
DOI: 10.1177/1369433220904013
|View full text |Cite
|
Sign up to set email alerts
|

Human-induced vibration of cold-formed steel floor systems: Parametric studies

Abstract: Designing a lightweight floor to prevent annoying vibrations induced by human activities is still a challenge because numerous factors need to be considered. In consequence, there is still a lack of reliable models and adequate design guidelines pertinent to the vibration serviceability of cold-formed steel floor systems. To facilitate understanding the fundamental concepts of lightweight floor vibrations for serviceability design, a newly proposed damped plate-oscillator model was adopted in this research to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[1,2]. This can be explained due to the fact that these human activities present excitation frequencies close to natural frequencies values of most structures, in the range of 4 Hz to 8 Hz [1][2][3][4][5][6]. This way, in this research work the main objective is to evaluate the people-structure dynamic interaction effect on the structural behaviour of building floors, through the development of experimental tests and numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. This can be explained due to the fact that these human activities present excitation frequencies close to natural frequencies values of most structures, in the range of 4 Hz to 8 Hz [1][2][3][4][5][6]. This way, in this research work the main objective is to evaluate the people-structure dynamic interaction effect on the structural behaviour of building floors, through the development of experimental tests and numerical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Reports show that structures with high fundamental frequencies, represented by timber floors, behave completely different compared with structures that have low fundamental frequencies (Hu, 2000; Onysko, 1986). Because of their high fundamental frequencies and high damping ratios, the responses are usually characterized by a series of impulses corresponding to the continuous steps of occupants, instead of being dominated by near-resonant vibration (Zhang and Xu, 2020). The features of an impulse, i.e., peak or root-mean-square value, are usually not much affected by previous or following impulses.…”
Section: Introductionmentioning
confidence: 99%
“…Venuti et al [21] demonstrated that, in addition to the dynamic structure-pedestrian interaction, it is also important to analyse the different walking paths that can be performed by users, as well as speed and step length. Following this same line of study, Zhang and Xu [22] carried out a parametric analysis in order to determine the difference in floor responses associated with four walking paths: parallel and perpendicular to the floor beams, diagonal and circular. The authors concluded that the path leads to the greatest responses depends on the floor attachment conditions.…”
Section: Introductionmentioning
confidence: 99%